Evaluation of Effect of Triterpenes and Limonoids on Cell Growth, Cell Cycle and Apoptosis in Human Tumor Cell Lines - M. Cazal, Cristiane; Choosang, Kantima; Gisele P. Severino, Vanessa; S. Soares, Marcio; Lucio F. Sarria, Andre; B. Fernandes, Joao; Fatima G.F. Silva, Maria; Cezar Vieira, Paulo; Pakkong, Pannee; M. Almeida, Gabriela; Helena Vasconcelos, M.; S.J. Nascimento, Maria; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2010)
Six triterpenes and eight limonoids were evaluated for their capacity to inhibit the growth of three human tumour cell lines, breast adenocarcinoma (MCF-7), non-small cell lung cancer (NCI-H460) and melanoma (A375-C5). The mechanisms involved in the observed cell growth arrest of the four most potent compounds were carried out by studying their effect in cell cycle profile and programmed cell death. The results showed that one triterpene (odoratol) and two limonoids (gedunin and cedrelone) caused cell cycle arrest while only the limonoids gedunin and cedrelone were found to be very potent inducers of apoptosis.
Keywords: melanoma